2013
DOI: 10.1530/eje-13-0436
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of a ghrelin test for the diagnosis of GH deficiency after subarachnoid hemorrhage

Abstract: ObjectiveTo determine the diagnostic value of a ghrelin test in the diagnosis of GH deficiency (GHD) shortly after aneurysmal subarachnoid hemorrhage (SAH).DesignProspective single-center observational cohort study.MethodsA ghrelin test was assessed after the acute phase of SAH and a GH-releasing hormone (GHRH)–arginine test 6 months post SAH. Primary outcome was the diagnostic value of a ghrelin test compared with the GHRH–arginine test in the diagnosis of GHD. The secondary outcome was to assess the safety o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…The majority of them were prospective single-centre studies (N = 15, 75 %), two were prospective multi-centric Criteria for diagnosis of endocrine abnormality differed widely, and included both basal hormone levels and stimulation tests ( Table 2). Five authors studied just a single hormonal axis (somatotropic [10], or adrenal axis [13,[26][27][28]) and the remaining studied multiple hormone alterations.…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…The majority of them were prospective single-centre studies (N = 15, 75 %), two were prospective multi-centric Criteria for diagnosis of endocrine abnormality differed widely, and included both basal hormone levels and stimulation tests ( Table 2). Five authors studied just a single hormonal axis (somatotropic [10], or adrenal axis [13,[26][27][28]) and the remaining studied multiple hormone alterations.…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…The occurrence and course of PD after SAH in the present study have been described elsewhere . Eight respondents with PD in our study suffered from GHD.…”
Section: Resultsmentioning
confidence: 82%
“…Blijdorp et al prospectively analysed 84 patients and reported preliminary data of 43 patients using basal hormonal tests, synacten test when ACTH deficiency was suspected and a ghrelin test in the early phase after SAH and confirmatory GHRH-arg test after six months [ 42 ]. The most prominent methodological shortcomings were the incomplete reports of patient selection [ 17 , 32 , 33 , 35 , 37 , 46 ], selection bias [ 17 , 33 - 35 , 42 , 46 ] and inadequate laboratory testing [ 17 , 33 , 35 , 36 , 38 , 43 , 44 ]. Some studies did not use dynamic tests to determine growth hormone or corticotrophin deficiency [ 17 , 34 , 43 , 44 , 46 ].…”
Section: Resultsmentioning
confidence: 99%